An Iterative Algorithm for Solving Fixed Point Problems and Quasimonotone Variational Inequalities - Tzu-Chien Yin; Yan-Kuen Wu; Ching-Feng Wen (Journal of Mathematics)
In this paper, we survey a common problem of the fixed point problem and the quasimonotone variational inequality problem in Hilbert spaces. We suggest an iterative algorithm for finding a common element of the solution of a quasimonotone variational inequality and the fixed point of a pseudocontractive operator. Convergence theorems are shown under some mild conditions. Several corollaries are also obtained.